Impact of a policy rate cut on bank profitability and financial stability - Sunjoo Hwang (Korea Development Institute (KDI), 2020)
Concerns prevail that a policy rate cut could weaken bank profitability and trigger financial instability. However, banks can sustain relatively high net interest margins with little fluctuation despite a rate cut owing to their dominant position in the deposit market and ability to adjust loan maturity. - By virtue of their market dominance, banks set their deposit rates below the base rate by a fixed percentage, and as such, the former falls within a narrower range than the latter. - Because deposit rates are little exposed to base rate fluctuations, banks are able to increase their share of long-term loans which are unaffected by short-term rate changes. This means that lending rates also fall by a smaller margin. - An empirical analysis found that a 1%p change in the call rate, which moves in line with the base rate, adjusts the deposit and lending rates by 0.53%p and 0.58%p, respectively, indicating that the fluctuation (0.05%p) in the net interest margin is statistically insignificant. Therefore, the possibility of financial instability due to a deterioration in bank profitability on a rate cut by the central bank should not be deemed as a constraint.
Keywords: 330